The Positive Side of Maximization: Linking Maximization Tendency With Meaning in Life Through Time Perspectives - Ma, Min; Zhao, Na; Zhang, Li (Frontiers in Psychology, 2021)
The negative influence of maximization on well-being, i.e., the maximization paradox, has received increased attention. However, few studies have shown the link between maximization tendency and meaning in life, which is one type of well-being, and no empirical literature has examined the mechanisms between them. We conducted an online survey in China to test the relationship between maximization tendency and meaning in life. Participants (N=2987) were invited to report their maximization, time perspective, meaning in life, and other control variables and demographic variables. Multi-mediation path analysis was adopted in the data analysis. The results revealed that maximization was positively associated with meaning in life, which confirmed the positive aspect of the maximization tendency. Further analyses indicated that the time perspectives of past-positive and future mediated the positive relationship between maximization and meaning in life. In contrast, a present-fatalistic time perspective was a suppressor in the positive relationship. Our findings suggest that the maximization tendency has a positive aspect rather than the overall maximization paradox. An important means of elevating meaning in life is to encourage the time perspective of past-positive and future-oriented and reduce the present-fatalistic time perspective.